The collapse of a regional institution : the story of the East African Railways within the East African Community, 1967-1977 - Whang, Patrick (Department of Historical Studies, 2016)
This dissertation examines the deterioration and collapse of the East African Railways Corporation (EARC) during the time of the East African Community (EAC), 1967-1977. The EARC has a long history that stretched back to the beginnings of colonial settlement in the East African region. It survived two world wars and a global economic depression, but just a few years after the independence of East African nations in the early 1960s, the EARC rapidly disintegrated. This then leads to the main project question: What were the causes that contributed to the collapse of the EARC? In order to address this question, I traveled to Nairobi in June 2015 to explore two archival sources: the Kenya National Archives and the Kenya National Railway Museum Archives. Both proved to be an invaluable repository of primary source material. In particular the main documents found were the business records describing the operations of the EARC during the period in question. In addition, with the help of a librarian at the Daily Nation newspaper in Nairobi, I was able to access archived newspaper articles on the EARC dating back to the years of interest. With this data and along with secondary source material, I conducted an analysis that triangulated these sources to provide a holistic picture of the events that affected the EARC. The narrative therefore demonstrates that while many factors contributed to the failure of the EARC what ultimately determined this were the nationalistic tendencies of representatives of EAC member states that overcame any centripetal forces of regional unity. There were also several events that precipitated the downfall of the EARC but ultimately it was the financial crisis of 1974 that proved decisive. This so-called crisis stemmed from a failure of each region to remit funds toward headquarters to be able to continue rail operations. This episode could not be blamed solely on foreign exchange concerns as some scholars have claimed. Instead the crisis exposed the long simmering national divisions that had manifested during this period. Each of the EAC partner states desired equitable treatment. When some perceived that they could not receive this through the operations of regional institutions such as the EARC, they engaged in actions that paralyzed EARC operations. This culminated in the complete fracturing of the EARC by 1977. 3 Since the end of the twentieth century, the EAC has been reborn and even expanded upon to include new member states beyond the original three of Kenya, Uganda and Tanzania. The East African Railways have also risen from the ashes and in late 2013, the initiation of the expansion on the existing rail lines to reinvigorate the railways commenced. But have the lessons of the EARC been learnt to avoid a repeat of the emergence of regional disunity that caused its collapse? It remains to be seen.